A 5G mm-wave compact voltage-controlled oscillator in 0.25 µm pHEMT technology - Abdelhafid Es-saqy; Maryam Abata; Mahmoud Mehdi; Mohammed Fattah; Said Mazer; Moulhime El Bekkali; Catherine Algani (Institute of Advanced Engineering and Science, 2021)
A 5G mm-wave monolithic microwave integrated circuit (MMIC) voltage-controlled oscillator (VCO) is presented in this paper. It is designed on GaAs substrate and with 0.25 µm-pHEMT technology from UMS foundry and it is based on pHEMT varactors in order to achieve a very small chip size. A 0dBm-output power over the entire tuning range from 27.67 GHz to 28.91 GHz, a phase noise of -96.274 dBc/Hz and -116.24 dBc/Hz at 1 and 10 MHz offset frequency from the carrier respectively are obtained on simulation. A power consumption of 111 mW is obtained for a chip size of 0.268 mm2. According to our knowledge, this circuit occupies the smallest surface area compared to pHEMTs oscillators published in the literature.